Replicated State Machines Without Replicated Execution - Lee, Jonathan; Nikitin, Kirill; Setty, Srinath (IEEE Symposium on Security and Privacy, 2020)
This paper introduces a new approach to reduce end-to-end costs in large-scale replicated systems built under a Byzantine fault model. Specifically, our approach transforms a given replicated state machine (RSM) to another RSM where nodes incur lower costs by delegating state machine execution: an untrusted prover produces succinct cryptographic proofs of correct state transitions along with state changes, which nodes in the transformed RSM verify and apply respectively. To realize our approach, we build Piperine, a system that makes the proof machinery profitable in the context of RSMs. Specifically, Piperine reduces the costs of both proving and verifying the correctness of state machine execution while retaining liveness—a distinctive requirement in the context of RSMs. Our experimental evaluation demonstrates that, for a payment service, employing Piperine is more profitable than naive reexecution of transactions as long as there are > 104 nodes. When we apply Piperine to ERC-20 transactions in Ethereum (a real-world RSM with up to 105 nodes), it reduces per-transaction costs by 5.4× and network costs by 2.7×.